A REVIEW OF FISH DIVERSITY AND MANAGEMENT OF THE VJOSA BASIN: THE FIRST FREE FLOW RIVER PROTECTED AREA IN THE BALKANS - SHUMKA, SPASE; MUÇOLLARI, NERTILA (Innovare Journal of Agricultural Sciences, 2023)
Vjosa River, an ecologically important area and the last Europe free-flowing river, is an essential aquatic ecosystem for the Albanian ecological, social, and cultural aspects. Fish and other aquatic species are notable among livings composition found in this region. The river environment is unfortunately seriously threatened by the excessive use of its resources, and hence, the goal of this study was to examine the status of fish biodiversity and the demands of the ecosystem for management. The Vjosa river is home of at least 34 species of fishes inhabiting the river and delta system, of which 29 are native, including eight species endemic to the Balkans. With 12 species, Cyprinidae is by far the most specious family, followed by Mugilidae (five). Salmonidae and Acipenseridae are represented by 2 species each. The remaining ten families are represented by a single species. At least four species (Pseudorasbora parva, Oncorhynchus mykiss, Carassius spp., Gambusia holbrooki) were introduced into the Vjosa basin. The lower river reach is populated by other species as European eel (Anguilla anguilla), species of Family Mugilidae (Mugil cephalus, Liza ramada, Liza salienes, and Chelon labrosus), Seabream (Sparus aurata), Seabass (Dicentrarchus labrax), Flatfish (Platichthys flesus, common sole (Solea spp.), etc., while the resident species associated with saline water include numerically prevalent with the two species Atherina boyeri and Aphanius fasciatus showing presence and significance.